Design of Robust Control for Vehicle Steer-by-Wire System - Suha S. Husain; Mina Qays Kadhim; Abdulkareem Sh. Mahdi Al-Obaidi; Alaq F. Hasan; Amjad J. Humaidi; Dwi Novia Al Husaeni (Universitas Pendidikan Indonesia, 2023)
This study presented the design of a robust controller based on Integral Sliding Mode Control (ISMC) for controlling the Vehicle Steer-by-Wire (VSbW) system. The dynamic model of the VSbW system is first developed and then the design of ISMC has been conducted via the states of the system. The VSbW system has been described by two terms; one term represents the nominal model, which is free from nonlinearities, and the other term lumps the uncertainties in system parameters. The integral sliding mode controller has been designed for controlling the VSbW system. The control design consists of two parts. The first control part has addressed the nominal term of the system, while the second control part tackles and eliminates the effects of uncertainties and perturbation due to the uncertain term of the system. The numerical simulation has been conducted to show the robustness of ISMC and its capability to reduce the chattering effect in the control signal. In addition, a comparison study in performance has been conducted between the proposed controller and other controllers in the literature. We also carry out bibliometric analysis to see research trends. Based on our analysis, the number of publications regarding the keywords